Low levels of caries in aggressive periodontitis: A literature review - Srinivas Sulugodu Ramachandra (Saudi Dental Journal)
This article is a traditional literature review on caries levels in aggressive periodontitis. Aggressive periodontitis generally affects systemically healthy individuals aged <30 years (older individuals can also be affected) and is characterized by a young age of onset, rapid rate of disease progression, and familial aggregation of cases. Dental caries is caused by the dissolution of enamel by acid-producing bacteria present in the plaque biofilm, especially when the biofilm reaches critical mass due to improper oral hygiene. The association between caries level and aggressive periodontitis has long been debated. Initial research indicated that caries levels were high in patients with aggressive periodontitis, but high-quality studies have consistently shown that caries and aggressive periodontitis are inversely related. A recent in vitro study showed that Streptococcus mutans was killed more readily in the saliva of patients with aggressive periodontitis and Aggregatibacter actinomycetemcomitans positivity than in patients with A. actinomycetemcomitans negativity. Other mechanisms possibly explaining the inverse relationship between caries and aggressive periodontitis in cases of Down’s syndrome are also discussed in this literature review. The usefulness of caries level in the diagnosis of aggressive periodontitis in developing countries such as India, where the disease is diagnosed primarily on the basis of clinical and radiographic features and familial history is also discussed. Keywords: Dental caries, Aggressive periodontitis, Inverse relationship, Diagnosis